Kinematics Analysis and Simulation of A New Type of Hybrid Palletizing Robot based on MDH Model - Guo Ruifeng; Peng Guangyu; Yang Liu; Yuan Chaofeng (Jixie chuandong)
As a model adopted in robot kinematics,MDH model is hardly mentioned in domestic literature.The MDH model about rotating joint is introduced in detail,taking a new type of hybrid palletizing robot as example.The kinematics equations of the robot are deduced by combining solving solely through reference coordinate system with homogeneous transformation solution.The 5-3-5 method is used in trajectory planning,and the program is written by using MATLAB,corresponding kinematics simulation is completed in LMS Virtual.lab Motion.The correctness of theoretical derivation is verified through comparing the results of simulation with calculation.It provides a theoretical basis for establishing robot kinematics precision model and make up the lack of MDH model in domestic literature.